1999
DOI: 10.1128/cdli.6.2.224-230.1999
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Serological Analysis of Lipoprotein LppA in Mycoplasma mycoides subsp. mycoides LC and Mycoplasma mycoides subsp. capri

Abstract: The genes encoding the 62-kDa lipoproteins from theMycoplasma mycoides subsp. mycoideslarge-colony type (LC) strain Y-goat and the M. mycoidessubsp. capri strain PG3 were cloned and analyzed by sequencing. These two lipoproteins have been named LppA[MmymyLC] and LppA[Mmyca], and their corresponding genes have been namedlppA[MmymyLC] and lppA[Mmyca], respectively. The nucleotide and deduced amino acid sequences of these two lipoproteins showed a very high degree of similarity between these two mycoplasmas. Give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Although early DNA-DNA hybridization studies by Askaa et al (1978) suggested that Mmc was closer to MmmSC than to MmmLC, analyses of 1D and 2D PAGE protein patterns proved the opposite (Costas et al, 1987;Leach et al, 1989;Olsson et al, 1990;Rodwell, 1982;Salih et al, 1983). Identification using a DNA probe (Taylor et al, 1992) and analysis of LppA sequence similarity and serological cross-reactions (Monnerat et al, 1999) also suggested a very close relatedness between MmmLC and Mmc, and two phylogenetic studies of the M. mycoides cluster concluded that they should be grouped into a single entity (Pettersson et al, 1996;Thiaucourt et al, 2000). However, the International Committee on Systematics of Prokaryotes Subcommittee on the taxonomy of Mollicutes has indicated that additional comparative analysis is required in order to clarify this matter (Johansson & Bradbury, 2007).…”
Section: Assessment Of the Concordance Of Individual Gene Trees With mentioning
confidence: 99%
See 2 more Smart Citations
“…Although early DNA-DNA hybridization studies by Askaa et al (1978) suggested that Mmc was closer to MmmSC than to MmmLC, analyses of 1D and 2D PAGE protein patterns proved the opposite (Costas et al, 1987;Leach et al, 1989;Olsson et al, 1990;Rodwell, 1982;Salih et al, 1983). Identification using a DNA probe (Taylor et al, 1992) and analysis of LppA sequence similarity and serological cross-reactions (Monnerat et al, 1999) also suggested a very close relatedness between MmmLC and Mmc, and two phylogenetic studies of the M. mycoides cluster concluded that they should be grouped into a single entity (Pettersson et al, 1996;Thiaucourt et al, 2000). However, the International Committee on Systematics of Prokaryotes Subcommittee on the taxonomy of Mollicutes has indicated that additional comparative analysis is required in order to clarify this matter (Johansson & Bradbury, 2007).…”
Section: Assessment Of the Concordance Of Individual Gene Trees With mentioning
confidence: 99%
“…Additional evidence has recently been presented by Vilei et al (2006) based on rpoB sequence comparisons. In the present work, comparisons have been extended to five genes using a similar sample of strains, though strain WK354, included as an Mmc strain in previous studies (Monnerat et al, 1999;Thiaucourt et al, 2000), was characterized in this work as MmmLC by both growth inhibition and dot immunobinding techniques. As in previous studies, the data obtained in this work show that MmmLC is closer to Mmc than to the biotype MmmSC and that MmmLC and Mmc are not sufficiently distant to constitute separate entities.…”
Section: Assessment Of the Concordance Of Individual Gene Trees With mentioning
confidence: 99%
See 1 more Smart Citation
“…The main problem in eradication is the frequent occurrence of sub asymptomatic infections and the persistence of chronic carriers after the clinical phase. Serological analysis is the most important diagnostic tool for the control of CBPP, but it is significantly hampered by the relatively low sensitivity and specificity of the methods (Abdo et al al., 2003;Vilei et al, 2000;Monnerat et al Contagious Bovine Pleuropneumonia (CBPP) is both an epidemic and endemic disease of cattle that affects production through mortality and reduction in product It also retards genetic improvement and limits working ability of cattle (Tambi and Maina, 2004). Accordingly, cattle in CBPP-infected areas (epidemic and endemic) are divided into three classes namely, calves and yearlings below 3 years, adult males and reproductive females.…”
Section: Introductionmentioning
confidence: 99%
“…The first two regions (D1 and D2) encode enzymes and putative glycerol transporters involved in the production of hydrogen peroxide using the glycerol-dependent metabolism of mycoplasmas (10). The region D3 encodes major antigens (LppA/P72) in Mycoplasma mycoides (21) that induced T cell responses early in infection (22). The region D4 includes an integrative conjugative element (ICE), the MIB-MIP system (9) and the F1-likeX0 ATPase (15).…”
Section: Discussionmentioning
confidence: 99%